2019
DOI: 10.3390/ijms20194745
|View full text |Cite
|
Sign up to set email alerts
|

Proton Therapy and Src Family Kinase Inhibitor Combined Treatments on U87 Human Glioblastoma Multiforme Cell Line

Abstract: Glioblastoma Multiforme (GBM) is the most common of malignant gliomas in adults with an exiguous life expectancy. Standard treatments are not curative and the resistance to both chemotherapy and conventional radiotherapy (RT) plans is the main cause of GBM care failures. Proton therapy (PT) shows a ballistic precision and a higher dose conformity than conventional RT. In this study we investigated the radiosensitive effects of a new targeted compound, SRC inhibitor, named Si306, in combination with PT on the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 76 publications
(85 reference statements)
4
38
0
Order By: Relevance
“…A new SRC inhibitor, belonging to the pyrazolo[3¨ -d] pyrimidines series (i.e., Si306, Lead Discovery Siena, Italy) showed an excellent pharmacodynamic profile and was able to significantly inhibit GBM cell growth in highly P-gp expressing cells as compared to dasatinib [ 116 ]. We previously demonstrated that Si306 showed a synergic radiosensitive effect with proton irradiation in GBM cell lines [ 117 ]. We also identified up- or down-regulated genes associated with the SRC pathway modulation in GBM cells after irradiation with proton therapy [ 117 ].…”
Section: New Frontiers To Improve Radiotherapy: Evaluating the Potmentioning
confidence: 99%
See 2 more Smart Citations
“…A new SRC inhibitor, belonging to the pyrazolo[3¨ -d] pyrimidines series (i.e., Si306, Lead Discovery Siena, Italy) showed an excellent pharmacodynamic profile and was able to significantly inhibit GBM cell growth in highly P-gp expressing cells as compared to dasatinib [ 116 ]. We previously demonstrated that Si306 showed a synergic radiosensitive effect with proton irradiation in GBM cell lines [ 117 ]. We also identified up- or down-regulated genes associated with the SRC pathway modulation in GBM cells after irradiation with proton therapy [ 117 ].…”
Section: New Frontiers To Improve Radiotherapy: Evaluating the Potmentioning
confidence: 99%
“…We previously demonstrated that Si306 showed a synergic radiosensitive effect with proton irradiation in GBM cell lines [ 117 ]. We also identified up- or down-regulated genes associated with the SRC pathway modulation in GBM cells after irradiation with proton therapy [ 117 ]. After 2 or 10 Gy irradiation with protons, we detected that the GBM cell cycle, motility, survival, and proliferation rate were strongly affected by Si306, also showing increased overall radiation efficiency [ 117 ].…”
Section: New Frontiers To Improve Radiotherapy: Evaluating the Potmentioning
confidence: 99%
See 1 more Smart Citation
“…from which we obtained the α[ ] and β[ ] parameters, extracted from the fit with their own standard deviation, and where S(0) is the zero-dose surviving fraction, obtained from a previous second-order fit, and as previously described [28].…”
Section: Clonogenic Survival Assay Dose Response Curves and Alfa Anmentioning
confidence: 99%
“…This plasmid contains the doxycycline-inducible TRE3G promoter (P TRE3G ) and a TK-green fluorescent protein (GFP) fusion protein coding sequence. Furthermore, previous studies have revealed that combination gene therapies exert additive or synergistic effects on brain tumors [15,16]. Accordingly, we have left an EcoRI cloning site of pTRE3G-TKGFP available for the insertion of other therapeutic genes to cooperate with the TK/GCV system in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%